Haemostatic testing prior to elective surgery in children? Not always! - Bidlingmaier, C.; Eberl, W.; Knöfler, R.; Olivieri, M.; Kurnik, K. (Hämostaseologie, 2009)
In Germany, preoperative coagulation tests are commonly used, based on the belief that these tests should identify patients with an increased bleeding risk. However, published evidence does not longer support this approach for both traditional screening tests and novel techniques of global assessment of haemostasis. Unselected screening yields many false positive results and detects irrelevant disorders. It leads to postponement of surgery, anxiety in parents and patients, and is not cost effective. Even worse, it does not reliably detect relevant bleeding disorders such as the most common coagulopathy, von Willebrand disease. The bleeding history of patients and their relatives is a more effective tool to detect patients at risk. According to international guidelines and a joint statement of different German medical societies, a standardized questionnaire should be mandatory in preoperative screening. A diagnostic pathway should be employed to identify patients in whom specific tests are helpful. Because neither laboratory tests nor questionnaires can infallibly predict or exclude perioperative bleeding, guidelines for the management of these unexpected situations have to be established.
Keywords: Coagulation tests